Zoledronate-induced orbital and ocular inflammation - Dyrda, Julia; Starkowska, Karolina (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
Orbital inflammation is one of numerous adverse effects of bisphosphonates. The symptoms include palpebral oedema, conjunctival chemosis, ocular motility impairment, proptosis and decreased visual acuity. This condition may coincide with other ocular adverse effects, as presented in this case report of a patient who developed orbital inflammation along with scleritis and uveitis after the administration of zoledronic acid for bone metastases of prostate cancer. He was admitted to the hospital with severely decreased visual acuity (hand motion) and massive oedema and proptosis. Following the execution of diagnostic imaging, intravenous steroids (methylprednisolone 0.5 g for 3 days) were introduced, leading to rapid alleviation of symptoms. At discharge the patient presented full recovery of visual acuity, which is typical for bisphosphonate ocular adverse effects treated with steroids.